2021
DOI: 10.3390/atmos12121618
|View full text |Cite
|
Sign up to set email alerts
|

A Machine-Learning Approach Combining Wavelet Packet Denoising with Catboost for Weather Forecasting

Abstract: Accurate forecasting of future meteorological elements is critical and has profoundly affected human life in many aspects from rainstorm warning to flight safety. The conventional numerical weather prediction (NWP) sometimes leads to unsatisfactory performance due to inappropriate initial state settings. In this paper, a short-term weather forecasting model based on wavelet packet denoising and Catboost is proposed, which takes advantage of the fusion information combining the historical observation data with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 29 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…Assuming we have a dataset S = {(X i , Y i )} i=1 ... n , where X i = (x i , 1 , ..., x i , m ) represents a vector of m features, and Y i ∈ R is the label value [102]. In the Greedy TS method, the categorical features are replaced with the average label value of the entire training set [103]. Therefore, x i , k is replaced with…”
Section: Algorithm 3 Lightgbmmentioning
confidence: 99%
“…Assuming we have a dataset S = {(X i , Y i )} i=1 ... n , where X i = (x i , 1 , ..., x i , m ) represents a vector of m features, and Y i ∈ R is the label value [102]. In the Greedy TS method, the categorical features are replaced with the average label value of the entire training set [103]. Therefore, x i , k is replaced with…”
Section: Algorithm 3 Lightgbmmentioning
confidence: 99%
“…Second, compared with the single crop coefficient model, the machine learning model can use the entire data set for training, minimize information loss, and still provide high prediction accuracy in the case of missing variables. Kim et al [32] proposed a CNN-CatBoost hybrid model solar radiation prediction method and concluded that the prediction accuracy and stability of this hybrid model is better than the single model of CNN and CatBoost; Niu et al [33] introduced a machine learning method based on wavelet packet denoising and CatBoost for weather forecasting. Using a feature selection and spatio-temporal feature addition to improve forecasting performance, the results show that the CatBoost model combined with wavelet packet denoising can achieve shorter convergence time and higher forecasting accuracy than forecasting models using deep learning or machine learning algorithms alone.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, machine learning (ML) architectures, applied to weather forecasting, can be grouped into static and dynamic (recurrent) in terms of whether the prediction is generated sequentially [48]- [51], or not. Static ML architectures include clustering (K-means, PCA) [52], [53], artificial neural networks (ANN) [49], [54], [55], graph neural networks (GNN) [56], clustering + neural networks [57], [58], decision trees such as Gradient Boosting (XGBoost [59], AdaBoost [50], CatBoost [50], [60], [61]), and Random Forest [62], [63]. On the other hand, dynamic ML architectures for weather forecasting make use of the sequential nature of training data in generating the forecast.…”
Section: Related Workmentioning
confidence: 99%